Effects of anodal transcranial direct current stimulation on implicit motor learning and language‐related brain function: An fMRI study. Issue 6 (10th March 2021) - Nakashima, Soichiro; Koeda, Michihiko; Ikeda, Yumiko; Hama, Tomoko; Funayama, Takuya; Akiyama, Tomomi; Arakawa, Ryosuke; Tateno, Amane; Suzuki, Hidenori; Okubo, Yoshiro
Abstract : Aim: Anodal transcranial direct current stimulation (tDCS) over the left dorsolateral prefrontal cortex (DLPFC) is known as a useful application for improving depressive symptoms or cognitive performance. Antidepressive effects by anodal tDCS over the left DLPFC are expected, but the neural mechanisms of these effects are still unclear. Further, in depression, reduced performance and left prefrontal hypofunction during the verbal fluency task (VFT) are generally known. However, few studies have examined the effect of tDCS on the language‐related cerebral network. We aimed to investigate whether anodal tDCS at the left DLPFC affects cognitive performance and the neural basis of verbal fluency. Methods: Nineteen healthy volunteers participated in this study. The effects of tDCS on cognitive behavior and cerebral function were evaluated by (i) performance and accuracy of implicit/explicit motor learning task (serial reaction time task/sequential finger‐tapping task), and (ii) cerebral activation while the subjects were performing the VFT by using a functional MRI protocol of a randomized sham‐controlled, within‐subjects crossover design. Results: Reaction times of the implicit motor learning task were significantly faster with tDCS in comparison with the sham. Further, language‐related left prefrontal‐parahippocampal‐parietal activation was significantly less with tDCS compared with the sham. Significant correlation was observed between shortened response time in serial reaction time task and decreased cerebral activation during VFT with tDCS. Conclusion: Anodal tDCS over the left DLPFC could improve cognitive behavior of implicit motor learning by improving brain function of the frontoparietal‐parahippocampal region related to motor learning, as well as language‐related regions.